Phosphoinositide 3-kinase: friend and foe in cardiovascular disease - Ghigo, Alessandra; Li, Mingchuan (Frontiers in Pharmacology, 2015)
Class I phosphoinositide 3-kinases (PI3Ks) are a family of lipid kinases activated by cell membrane receptors, either receptor tyrosine kinases (RTKs) or G protein-coupled receptors (GPCRs), to catalyze the production of the lipid second messenger phosphatidylinositol (3,4,5)-trisphosphate (PIP3). These enzymes engage multiple downstream intracellular signaling pathways controlling cell proliferation, survival and migration. In the cardiovascular system, the four class I PI3K isoforms, PI3Kα, PI3Kβ, PI3Kδ and PI3Kγ are differentially expressed in distinct cell subsets which include cardiomyocytes, fibroblasts, endothelial and vascular smooth muscle cells as well as leukocytes, suggesting specific functions for distinct PI3K isoenzymes. During the last decades, genetic disruption studies targeting different PI3K genes have elucidated the contribution of specific isoenzymes to cardiac and vascular function regulation, highlighting both beneficial and maladaptive roles. New layers of complexity in the function of PI3Ks have recently emerged, indicating that distinct PI3K isoforms are interconnected by various crosstalk events and can function not only as kinases, but also as scaffold proteins coordinating key signalosomes in cardiovascular health and disease. In this review, we will summarize major breakthroughs in the comprehension of detrimental and beneficial actions of PI3K signaling in cardiovascular homeostasis, and we will discuss recently unraveled cross-talk and scaffold mechanisms as well as the role of the less characterized class II and III PI3K isoforms.